Preparation method and application of glass bead-based floatable photocatalyst

By combining glass microbeads with a double network hydrogel formed by ionic cross-linking of sodium alginate and hydroxymethyl chitosan, a floating platform is prepared and loaded with catalysts, which solves the problem of difficult agglomeration and recycling of traditional powdered photocatalysts. , improves the efficiency and stability of the photocatalytic reaction, and simplifies the catalyst recovery process.

CN119327486APending Publication Date: 2025-01-21ZHENGZHOU UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411506222.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-28
Publication Date
2025-01-21

AI Technical Summary

Technical Problem

Traditional powder photocatalysts are prone to agglomeration during use, reducing the efficiency of photocatalytic reactions, and difficult recycling, resulting in waste of resources and environmental pollution.

Method used

By combining glass microbeads with a double network hydrogel formed by ionic cross-linking of sodium alginate and hydroxymethyl chitosan, a floating platform is prepared, and the catalyst is uniformly loaded on the platform to form a glass microbead-based Floating photocatalyst.

Benefits of technology

This method effectively avoids the agglomeration of the catalyst, improves the efficiency and stability of the photocatalytic reaction, simplifies the recycling process of the catalyst, and reduces environmental pollution.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119327486A_ABST
    Figure CN119327486A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a glass bead-based floatable photocatalyst, which comprises the following steps: mixing a sodium alginate homogeneous solution and a hydroxymethyl chitosan homogeneous solution to obtain a mixed solution; adding glass beads into the mixed solution, uniformly stirring, and drying and shaping in a mold to obtain a floatable platform; adding ZnIn2S4 into the mixed solution, and stirring to obtain uniformly dispersed sol; and finally, uniformly spin-coating the sol on a shaped floatable platform, then drying and demolding, and placing the platform in a calcium chloride aqueous solution for crosslinking to obtain the glass bead-based floatable photocatalyst. The prepared floatable photocatalyst is located at a solid-liquid-gas three-phase interface, provides proper reaction conditions for an oxidation reaction and a reduction reaction, improves the reaction efficiency of a photocatalytic reaction, avoids agglomeration of the powdery photocatalyst, and exposes more active sites.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of energy materials, and in particular to a preparation method and application of a glass microbead-based floating photocatalyst. Background Art

[0002] As global environmental problems become increasingly severe and the energy crisis continues to intensify, the development of efficient and environmentally friendly photocatalytic technology has become a research hotspot. In the field of photocatalysis, although traditional powdered photocatalysts can achieve photocatalytic reactions to a certain extent, they also have many disadvantages.

[0003] On the one hand, traditional powder photocatalysts are prone to agglomeration during use. Due to the interaction between powder particles, the catalyst particles will aggregate together, resulting in a reduction in specific surface area and the masking of active sites, which greatly reduces the efficiency of the photocatalytic reaction. In addition, the agglomerated powder photocatalyst is unevenly dispersed in the reaction system, which will also affect the stability and repeatability of the photocatalytic reaction.

[0004] On the other hand, traditional powder photocatalysts face the problem of difficult recycling in practical applications. Due to their fine particles, they are difficult to separate from the reaction system, which not only causes a waste of resources, but also may cause environmental pollution. In particular, for some toxic photocatalysts, if they cannot be effectively recycled, they will pose a serious threat to the ecological environment and human health.

[0005] At the same time, traditional powder photocatalysts are often in a single liquid phase or solid-liquid interface during photocatalytic reactions, and cannot fully utilize the advantages of the solid-liquid-gas three-phase. This limits the diffusion and transportation of gases during the reaction, and the supply of reactants and the release of reaction products are not smooth, which affects the efficiency of the photocatalytic reaction. Moreover, in aqueous solution, powder photocatalysts will also absorb part of the sunlight, reducing the efficiency of sunlight utilization. Summary of the invention

[0006] In order to solve the problem that traditional powder photocatalysts are prone to agglomeration during use and are difficult to recycle, the present invention uses a double network hydrogel formed by ionic crosslinking of sodium alginate and carboxymethyl chitosan to combine glass microbeads to form a floating platform, and evenly loads the catalyst on the platform.

[0007] The technical solution of the present invention is a method for preparing a glass microsphere-based floating photocatalyst, and the steps are as follows: (1) Dissolve 4.5 hydrated indium nitrate, anhydrous zinc acetate, citric acid, and thioacetamide in deionized water and stir evenly to obtain a precursor solution. Place the precursor solution in a reactor for hydrothermal reaction. After the hydrothermal reaction is completed, centrifuge, wash, dry, and grind the reaction product to obtain ZnIn 2 S4 powder; (2) Preparation of glass microbead-based floating platform: Sodium alginate and hydroxymethyl chitosan are dissolved in deionized water to obtain a sodium alginate homogeneous solution and a hydroxymethyl chitosan homogeneous solution, respectively, and then the sodium alginate homogeneous solution and the hydroxymethyl chitosan homogeneous solution are mixed and stirred to obtain a mixed solution; (3) adding glass microbeads to the mixed solution obtained in step (2) and stirring evenly, and then placing the mixture in a mold to dry and shape, thereby obtaining a floating platform; (4) ZnIn obtained in step (1) 2 S 4 Adding to the mixed solution of step (2) and stirring to obtain a uniformly dispersed sol; (5) The sol of step (4) is evenly spin-coated on the floatable platform formed in step (3), and then dried and demolded. The platform is then placed in a calcium chloride aqueous solution for cross-linking to obtain a glass microbead-based floatable photocatalyst.

[0008] The stirring time in step (1) is 30-60 min, the hydrothermal temperature is 140-180° C., the hydrothermal reaction time is 1-3 h, the centrifugal cleaning solution is anhydrous ethanol and deionized water, and the sample is ground in an agate mortar for 30-60 min after drying.

[0009] In the step (2), sodium alginate and hydroxymethyl chitosan are dissolved in deionized water respectively, and stirred for 1-3 hours to obtain a sodium alginate homogeneous solution and a hydroxymethyl chitosan homogeneous solution. The sodium alginate homogeneous solution and the hydroxymethyl chitosan homogeneous solution are then mixed and stirred for 0.2-2 hours to obtain a mixed solution. The mixed solution is used in the steps (3) and (4) respectively. The mass concentration of the sodium alginate homogeneous solution is 20 g / L, and the mass concentration of the hydroxymethyl chitosan homogeneous solution is 20 g / L. The volume ratio of the sodium alginate homogeneous solution to the hydroxymethyl chitosan homogeneous solution is (1:2)-(2:1).

[0010] In the step (3), the mass volume ratio of the glass microspheres to the mixed solution is 1.2:5-20.

[0011] In the step (3), the mold material is a silicone rubber mold or a polytetrafluoroethylene mold, the drying temperature is 70-90°C, the drying time is 2-6 hours, and the mold is not demoulded after drying.

[0012] In step (4), ZnIn is loaded 2 S 4 The amount of ZnIn is 5-30 mg, and the amount of homogeneous solution is 5-10 mL. In order to facilitate transfer, a polytetrafluoroethylene centrifuge tube is used as a container, and in order to avoid 2 S 4If the dispersion is uneven, add the homogeneous solution first and then slowly add ZnIn 2 S 4 , stir for 30-60 min.

[0013] In step (5), the sol is spin-coated on the platform, and then placed in an oven at a drying temperature of 70-90°C for a drying time of 2-6 h. After drying, the platform is demoulded. After demoulding, the platform is placed in a 0.1-0.3 mol / L CaCl 2 The cross-linking in the solution is carried out for 6-12 hours to obtain a glass microsphere-based floatable photocatalyst having two different structures, consisting of a floatable glass microsphere layer at the bottom layer providing buoyancy and a photocatalytic layer loaded with photocatalyst at the top layer.

[0014] The prepared glass microbead-based floating photocatalyst is used in photocatalytic hydrogen production, carbon dioxide reduction, and pollutant degradation.

[0015] The beneficial effects of the present invention are as follows: The present invention provides a method for preparing a glass microsphere-based floating photocatalyst, wherein the prepared floating photocatalyst is located at the solid-liquid-gas three-phase interface, and provides suitable reaction conditions for oxidation and reduction reactions, thereby improving the reaction efficiency of the photocatalytic reaction, avoiding the agglomeration of powdered photocatalysts, and exposing more active sites. The specific beneficial effects are as follows: (1) Unique three-phase interface advantage: The floating photocatalyst is located at the solid-liquid-gas three-phase interface. This special location creates an extremely favorable environment for oxidation and reduction reactions. At the three-phase interface, the material transfer and reaction process are smoother, and the gas can diffuse and transport quickly to ensure sufficient supply of reactants. At the same time, the reaction products can also be released quickly, avoiding the situation where the reaction is inhibited by the accumulation of reaction products. This efficient material exchange mechanism allows more active sites to fully play their role, greatly improving the efficiency of the photocatalytic reaction.

[0016] (2) Enhanced utilization of sunlight: Compared with traditional powder photocatalysts, floating photocatalysts reduce the absorption of sunlight by aqueous solutions. In photocatalytic reactions, full utilization of sunlight is crucial. Traditional powder catalysts in aqueous solutions easily cause scattering and absorption of sunlight, reducing the effective light intensity. The floating platform of this invention cleverly avoids this problem, allowing more sunlight to irradiate the catalyst surface and stimulate the photocatalytic reaction, thereby significantly improving the utilization efficiency of sunlight and further promoting the progress of the photocatalytic reaction.

[0017] (3) Effectively prevent the agglomeration of catalyst powder: In this invention, the catalyst is loaded on a floating platform, and the hydrogel is used to evenly distribute the catalyst, thus preventing agglomeration. In this way, more active sites are exposed and can fully contact with the reactants, greatly improving the activity of the photocatalytic reaction.

[0018] (4) Convenient recycling method: For powdered catalysts, recycling is a thorny issue. Due to their small particles, they are difficult to separate from the reaction system, which not only causes a waste of resources, but also may cause environmental pollution. Floating photocatalysts have obvious advantages. Their large size and floatability make recycling easier. Through simple filtering or salvaging methods, the platform can be separated from the reaction system to achieve the recovery and reuse of the catalyst, reducing costs and also reducing the impact on the environment.

[0019] (5) The high-strength double-network hydrogel effectively reduces the shedding of photocatalysts and avoids some toxic photocatalysts from polluting water bodies. In addition, the materials used in the glass microbead-based floating photocatalysts are non-toxic and non-polluting, which is of great significance for environmental protection and sustainable development. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 A physical picture of the glass microsphere-based floating photocatalyst prepared in Example 1 and a demonstration of its application scenario; Figure 2 This is an optical microscope image of the glass microsphere-based floating photocatalyst prepared in Example 1; Figure 3 The photocatalytic performance of the glass microsphere-based floating photocatalyst prepared in Example 1 and the traditional powder photocatalyst was tested; Figure 4 The catalyst ZnIn in the glass microsphere-based floating photocatalyst prepared in Example 1 2 S 4 XRD pattern of Figure 5 The photocatalytic activity of titanium dioxide in different forms is analyzed in Example 4; Figure 6 This is the scanning spectrum of microbeads loaded with titanium dioxide in Example 4; Figure 7 This is the XRD spectrum of the microbeads loaded with titanium dioxide in Example 4. DETAILED DESCRIPTION

[0021] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0022] The glass microsphere-based floating photocatalyst disclosed in the present invention is applied to photocatalytic hydrogen production, carbon dioxide reduction, and organic pollutant degradation.

[0023] A method for preparing a glass microsphere-based floating photocatalyst comprises the following steps: (1) Dissolve 4.5 hydrated indium nitrate, anhydrous zinc acetate, citric acid, and thioacetamide in deionized water and stir evenly to obtain a precursor solution. Place the precursor solution in a reactor for hydrothermal reaction. After the hydrothermal reaction is completed, centrifuge, wash, dry, and grind the reaction product to obtain ZnIn 2 S 4 powder; (2) Preparation of glass microbead-based floating platform: Sodium alginate and hydroxymethyl chitosan are dissolved in deionized water to obtain a sodium alginate homogeneous solution and a hydroxymethyl chitosan homogeneous solution, respectively. The sodium alginate homogeneous solution and the hydroxymethyl chitosan homogeneous solution are then mixed. The mass concentration of the sodium alginate homogeneous solution is 20 g / L, and the mass concentration of the hydroxymethyl chitosan homogeneous solution is 20 g / L. The volume ratio of the sodium alginate homogeneous solution to the hydroxymethyl chitosan homogeneous solution is (1:2)-(2:1). After stirring evenly, a mixed solution is obtained. (3) adding glass microbeads to the mixed solution obtained in step (2) and stirring evenly, and then placing the mixture in a mold to dry and shape, thereby obtaining a floating platform; (4) ZnIn obtained in step (1) 2 S 4 Adding to the mixed solution of step (2) and stirring to obtain a uniformly dispersed sol; (5) The sol of step (4) is evenly spin-coated on the floatable platform formed in step (3), and then dried and demolded. The platform is then placed in a calcium chloride aqueous solution for cross-linking to obtain a glass microbead-based floatable photocatalyst.

[0024] Example 1 The steps for preparing a glass microbead-based floating photocatalyst with a sol-to-microbead mass ratio of 1:3 are as follows: (1) Photocatalyst ZnIn 2 S 4Preparation of powder: Weigh 382 mg of 4.5 hydrated indium nitrate, 182 mg of anhydrous zinc acetate, 1.01 g of citric acid, and 450 mg of thioacetamide and dissolve them in 30 mL of deionized water and stir evenly to obtain a precursor solution. Place the precursor solution in a reactor and heat it at 160°C for 2 h. After the reaction is completed, centrifuge, wash, dry, and grind the reaction product to obtain ZnIn 2 S 4 powder; (2) Preparation of glass microbead-based floating platform: Weigh 200 mg of sodium alginate and 200 mg of carboxymethyl chitosan and dissolve them in 10 mL of deionized water respectively, stir evenly to obtain a homogeneous solution of sodium alginate and CMC. Then mix the homogeneous solution of sodium alginate and the homogeneous solution of CMC and stir evenly to obtain a mixed solution. Weigh 1.2 g of glass microbeads, measure 20 mL of the mixed solution, place it in a polytetrafluoroethylene beaker, mix evenly, pour it into a silicone rubber mold and dry it at 90 °C for 3 h to obtain a glass microbead-based floating platform; (3) Catalyst loading on glass microbead-based floating platform: Weigh 10 mg of the photocatalyst obtained in step (1), measure 5 mL of the mixed solution prepared in step (2), place it in a polytetrafluoroethylene container and stir it evenly, then spin-coat it on the platform formed in step (2), dry it and demold it. Weigh 0.55 g of anhydrous calcium chloride and dissolve it in 50 mL of deionized water to obtain 0.1 mol / L CaCl 2 Solution. The shaped platform loaded with photocatalyst was placed in a calcium chloride aqueous solution for cross-linking for 24 h to obtain a glass microsphere-based floating photocatalyst. The obtained glass microspheres have a particle size of 30-100 μm, a platform thickness of 2-3 mm, and a photocatalytic layer thickness of about 0.1 mm. Figure 1-4 .

[0025] Example 2 The steps for preparing a glass microbead-based floating photocatalyst with a sol-to-microbead mass ratio of 1:4 are as follows: (1) Photocatalyst ZnIn 2 S 4 Preparation of powder: Weigh 382 mg of 4.5 hydrated indium nitrate, 182 mg of anhydrous zinc acetate, 1.01 g of citric acid, and 450 mg of thioacetamide and dissolve them in 30 mL of deionized water and stir evenly to obtain a precursor solution. Place the precursor solution in a reactor and heat it at 160 °C for 2 h. After the reaction is completed, centrifuge, wash, dry, and grind the reaction product to obtain ZnIn 2 S 4 powder; (2) Preparation of glass microbead-based floating platform: Weigh 200 mg of sodium alginate and 200 mg of carboxymethyl chitosan and dissolve them in 10 mL of deionized water respectively, stir evenly to obtain SA and CMC homogeneous solutions. Then mix the SA homogeneous solution and the CMC homogeneous solution and stir evenly to obtain a mixed solution. Weigh 1.2 g of glass microbeads, measure 15 mL of the mixed solution, place it in a polytetrafluoroethylene beaker, mix evenly, pour it into a silicone rubber mold and dry it at 90 °C for 3 h to obtain a glass microbead-based floating platform; (3) Catalyst loading on glass microbead-based floating platform: Weigh 10 mg of the photocatalyst obtained in step (1) and take 5 mL of the mixed solution prepared in step (2) into a polytetrafluoroethylene container and stir evenly, then spin-coat it on the platform formed in step (2), dry it and demold it. Weigh 0.55 g of anhydrous calcium chloride and dissolve it in 50 mL of deionized water to obtain 0.1 mol / L CaCl 2 The shaped platform loaded with photocatalyst was placed in a calcium chloride aqueous solution for cross-linking for 24 h to obtain a glass microbead-based floating photocatalyst.

[0026] Example 3 The steps for preparing a glass microbead-based floating photocatalyst with a sol-to-microbead mass ratio of 1:6 are as follows: (1) Photocatalyst ZnIn 2 S 4 Preparation of powder: Weigh 382 mg of 4.5 hydrated indium nitrate, 182 mg of anhydrous zinc acetate, 1.01 g of citric acid, and 450 mg of thioacetamide and dissolve them in 30 mL of deionized water and stir evenly to obtain a precursor solution. Place the precursor solution in a reactor and heat it at 160 °C for 2 h. After the reaction is completed, centrifuge, wash, dry, and grind the reaction product to obtain ZnIn 2 S 4 powder; (2) Preparation of glass microbead-based floating platform: Weigh 200 mg of sodium alginate and 200 mg of carboxymethyl chitosan and dissolve them in 10 mL of deionized water respectively, stir evenly to obtain SA and CMC homogeneous solutions. Then mix the SA homogeneous solution and the CMC homogeneous solution and stir evenly to obtain a mixed solution. Weigh 1.2 g of glass microbeads, measure 10 mL of the mixed solution, place it in a polytetrafluoroethylene beaker, mix evenly, pour it into a silicone rubber mold and dry it at 90 °C for 3 h to obtain a glass microbead-based floating platform; (3) Catalyst loading on glass microbead-based floating platform: Weigh 10 mg of the photocatalyst obtained in step (1) and take 5 mL of the mixed solution prepared in step (2) into a polytetrafluoroethylene container and stir evenly, then spin-coat it on the platform formed in step (2), dry it and demold it. Weigh 0.55 g of anhydrous calcium chloride and dissolve it in 50 mL of deionized water to obtain 0.1 mol / L CaCl 2 The shaped platform loaded with photocatalyst was placed in a calcium chloride aqueous solution for cross-linking for 24 h to obtain a glass microbead-based floating photocatalyst.

[0027] From Examples 1-3, it can be concluded that, when the amount of microbeads remains unchanged, as the amount of sol increases, the integrity of the platform increases and it is not easy to disperse. However, the floatability decreases, and when the amount of sol is too much, cavities are easily generated during the drying process, and the platform morphology is difficult to control.

[0028] Example 4 The ZnIn prepared in step (1) 2 S 4 Powder replaced with TiO 2 The remaining steps are the same. Figure 5 It can be seen that TiO 2 The catalytic performance of the photocatalyst is improved by 90% compared with the traditional powdered photocatalyst. In addition, the catalytic performance of the floatable photocatalyst prepared by the present invention is comparable to that of the common floatable photocatalyst, but the catalyst exhibits higher stability. Figure 6 The SEM image shows that it was successfully prepared. Figure 7 It proves that the microbeads are successfully loaded with titanium dioxide. 2 S 4 The powder can also be replaced by CdS (metal sulfide), gC 3 N 4 wait.

[0029] The above is a detailed introduction to the preparation method and application of the glass microsphere-based floating photocatalyst provided by the present invention. This article uses specific examples to illustrate the principles and implementation methods of the present invention. The description of the above embodiments is only used to help understand the method of the present invention and its core idea. It should be pointed out that for ordinary technicians in this technical field, without departing from the principle of the present invention, several improvements and modifications can be made to the present invention, and these improvements and modifications also fall within the scope of protection of the claims of the present invention.

Claims

1. A method for preparing a glass microsphere-based floating photocatalyst, comprising the following steps: (1) dissolving 4.5 hydrated indium nitrate, anhydrous zinc acetate, citric acid and thioacetamide in deionized water and stirring the mixture to obtain a precursor solution, placing the precursor solution in a reactor for a hydrothermal reaction, and after the hydrothermal reaction is completed, centrifuging, washing, drying and grinding the reaction product to obtain ZnIn2S4 powder; (2) Preparation of glass microbead-based floating platform: Sodium alginate and hydroxymethyl chitosan are dissolved in deionized water to obtain a sodium alginate homogeneous solution and a hydroxymethyl chitosan homogeneous solution, respectively, and then the sodium alginate homogeneous solution and the hydroxymethyl chitosan homogeneous solution are mixed and stirred to obtain a mixed solution; (3) adding glass microbeads to the mixed solution obtained in step (2) and stirring evenly, and then placing the mixture in a mold to dry and shape, thereby obtaining a floating platform; (4) adding the ZnIn2S4 obtained in step (1) to the mixed solution in step (2) and stirring to obtain a uniformly dispersed sol; (5) The sol of step (4) is evenly spin-coated on the floatable platform formed in step (3), and then dried and demolded. The platform is then placed in a calcium chloride aqueous solution for cross-linking to obtain a glass microbead-based floatable photocatalyst.

2. The method for preparing a glass microsphere-based floating photocatalyst according to claim 1, characterized in that: In the step (1), the stirring time is 30-60 min, the hydrothermal temperature is 140-180° C., the hydrothermal reaction time is 1-3 h, the centrifugal cleaning solution is anhydrous ethanol and deionized water, and after drying, the sample is ground in an agate mortar for 30-60 min.

3. The method for preparing a glass microsphere-based floating photocatalyst according to claim 1, characterized in that: In the step (2), sodium alginate and hydroxymethyl chitosan are dissolved in deionized water respectively, and stirred for 1-3 hours to obtain a sodium alginate homogeneous solution and a hydroxymethyl chitosan homogeneous solution. The sodium alginate homogeneous solution and the hydroxymethyl chitosan homogeneous solution are then mixed and stirred for 0.2-2 hours to obtain a mixed solution. The mixed solution is used in step (3) and step (4), respectively.

4. The method for preparing a glass microsphere-based floating photocatalyst according to claim 1 or 3, characterized in that: The mass concentration of the sodium alginate homogeneous solution is 20 g / L, and the mass concentration of the hydroxymethyl chitosan homogeneous solution is 20 g / L. The volume ratio of the sodium alginate homogeneous solution to the hydroxymethyl chitosan homogeneous solution is (1:2)-(2:1).

5. The method for preparing a glass microsphere-based floating photocatalyst according to claim 1, characterized in that: In the step (3), the mass volume ratio of the glass microspheres to the mixed solution is 1.2:5-20.

6. The method for preparing a glass microsphere-based floating photocatalyst according to claim 1, characterized in that: In the step (3), the mold material is a silicone rubber mold or a polytetrafluoroethylene mold, the drying temperature is 70-90°C, the drying time is 2-6h, and the mold is not demoulded after drying.

7. The method for preparing a glass microsphere-based floating photocatalyst according to claim 1, characterized in that: The amount of ZnIn2S4 loaded in step (4) is 5-30 mg, and the amount of the homogeneous solution is 5-10 mL.

8. The method for preparing a glass microsphere-based floating photocatalyst according to claim 1, characterized in that: In the step (5), the sol is spin-coated on the platform, and then placed in an oven at a drying temperature of 70-90°C for a drying time of 2-6 h. After drying, the platform is demoulded. After demoulding, the platform is placed in a 0.1-0.3 mol / L CaCl2 solution for cross-linking for 6-12 hours to obtain a glass microbead-based floating photocatalyst.

9. Use of the glass microsphere-based floatable photocatalyst prepared according to claims 1-8 in photocatalytic hydrogen production, carbon dioxide reduction, and pollutant degradation.